Transvaginal management of severe pelvic organ prolapse in nulliparous women. Issue 3 (4th February 2017) - Lo, Tsia‐Shu; Jaili, Sukanda; Uy‐Patrimonio, Ma. Clarissa; Karim, Nazura bt; Ibrahim, Rami
Abstract: Aim: The aim of this study was to evaluate the management outcomes of advanced pelvic organ prolapse (POP) in nulliparous women. Methods: Eight nulliparous women diagnosed with POP ≥ stage 3 between January 2005 and August 2013, according to the Pelvic Organ Quantification System (POPQ), were reviewed. Seven were managed surgically and one was managed with pessary. Primary outcome was surgical objective cure (POP‐Q ≤ 1) and subjective cure, defined as negative response to questions 2 and 3 on Pelvic Organ Prolapse Distress Inventory 6. Secondary outcomes were complications, symptoms' severity and quality of life according to validated questionnaires. Results: A total of 1275 prolapse patients with POP‐Q ≥ stage 3 were managed surgically, among whom seven (0.55%) were nulliparous. Each woman had at least one risk factor associated with POP. Risk factors identified were history of pelvic trauma, obesity, menopause, chronic cough, hard physical labor and constipation. Five patients underwent surgical correction (vaginal hysterectomy with sacrospinous fixation) with mesh (Perigee, n = 3; Avaulta, n = 2). Two patients had uterine preservation without mesh (hysteropexy with sacrospinous ligament fixation). One patient preferred treatment with pessary. The total cure rate (objective and subjective cure rates) was 86% after surgical reconstructive surgery. Conclusion: Management of nulliparous advanced POP poses significant challenges with regard to uterine preservation, future pregnancy and childbirth. Conservative management with pessary insertion should be offered followed by surgical correction. Reconstructive surgery with mesh may improve prolapse symptoms objectively and subjectively.